ANTROPOSENTRISME PADA KEGIATAN EKSPLORASI PERTAMBANGAN ILEGAL DI KAWASAN HUTAN PROVINSI ACEH - sari, novita; hardiyanti, Siti; Fajri, Nurul (Journal of Political Sphere, 2023)
AbstractThe purpose of this study is to find out how anthropocentrism manifests in illegal mining exploration activities in the forest area of Aceh Province. The anthropocentrism studied is related to environmental ethics in carrying out mining exploration activities. The research used in this study uses a library research approach using data sources in the form of books, articles, websites, newspapers and reports. In the results of this study it was found that there is a real form of anthropocentrism in illegal mining activities carried out at several points such as in Pidie, Central Aceh, Aceh Jaya, West Aceh, Nagan Raya and South Aceh districts. This is evidenced by human actions that continue to extract natural resources without regard to the impacts, the fatality of mining exploration is also carried out in protected forest areas. Illegal mining occurs because of a lack of supervision from related parties, the negligence of those who manage it and the lack of licensing facilitation. the factor of unscrupulous persons carrying out illegal mining activities is to make ends meet and improve the economic standard. Mining makes business land for the eyes of its goods so that it has an impact on the destruction of forest ecosystems, environmental pollution, disease outbreaks and natural disasters, around 2,000 hectares of forest land has been damaged by this illegal mining. So this research is important to do to describe that there are anthropocentrism actions in legal mining exploration that can threaten environmental damage for the benefit of human business.